Case Series of Q Fever Infection: A 15-year Experience at Sultan Qaboos University Hospital, Oman - Kowthar S. Hassan; Batool Al Lawati; Turkiya Al-Siyabi (Oman Medical Journal)
Objectives: Q fever is a worldwide zoonosis, yet its prevalence may be underestimated due to the challenges in diagnosis. We present a series of cases where patients were treated for Q fever infection based primarily on their clinical features and available laboratory tests, highlighting the difficulties in establishing the diagnosis. Methods: This 15-year case series was observed from January 2009 to November 2023 at Sultan Qaboos University Hospital, Oman. Relevant patient information was obtained from the electronic hospital records under the ethical approval MREC # 3139. Results: We treated 17 patients from a total of 1481 patients tested. The median age was 38 years, with a male-to-female ratio of 1.4:1. Fever was the most common symptom, and six patients experienced weight loss. Hepatobiliary, respiratory, neurological, and musculoskeletal symptoms occurred in 10, six, five, and four patients, respectively. Three patients developed rashes during their illness. Two patients had definite infective endocarditis, one had probable infective endocarditis, and two patients had pericardial effusion. Conclusions: Q fever should be considered in the differential diagnosis of a wide range of clinical presentations. However, it can be clinically challenging, and serological test interpretation can be difficult in areas of endemicity and with limited diagnostic tests. A combination of compatible clinical illnesses and appropriate diagnostic tests is necessary for accurate diagnosis.